0113 Evaluating Closed-Loop Auditory Stimulation During Sleep as an Intervention to Improve Memory Consolidation Deficits in Schizophrenia. (27th May 2020) - Baxter, B; Kwok, K; Talbot, C; Zhu, L; Mylonas, D; Stickgold, R; Manoach, D
Abstract: Introduction: Converging evidence supports the hypothesis that reduced sleep spindles and spindle-slow oscillation (SO) coordination contribute to cognitive deficits in schizophrenia. Closed-loop auditory stimulation in healthy adults increases sleep spindles and improves declarative memory consolidation. Here we investigated whether closed-loop auditory stimulation also improves sleep-dependent procedural memory consolidation as a first step towards an intervention in schizophrenia. Methods: Thirteen healthy adults participated in two nap sessions (stimulation or detection only) with polysomnography in a counterbalanced order. Participants were trained on the finger tapping Motor Sequence Task (MST), which measures sleep-dependent motor procedural memory consolidation, prior to napping and were tested after awakening. We detected the negative peak of SOs during non-REM sleep and, in the stimulation condition, delivered 50ms of pink noise during the SO up-state. Results: Auditory stimulation increased SOs and spindles during the SO up-state in a frontocentral cluster of electrodes 800-1200ms after stimulation compared to detection only (p<0.05). Stimulation also showed promise for improving memory consolidation (33% increase in MST overnap improvement from detection-only) but this did not reach significance in this small sample and data collection is ongoing. Conclusion: Auditory stimulation evoked coordinated spindle-SO events that mediate memory consolidation, but more subjects are needed to evaluate whether it also improves memory. If it does, we will test the effects of stimulation on sleep-dependent memory deficits in patients with schizophrenia. Closed-loop auditory stimulation shows promise as a safe, scalable intervention for cognitive deficits that can be implemented at home with commercially available devices. Support: R01 MH67720 (DSM & RS), NIH-NHLBI 5T32HL007901-17 (BB), K24MH099421 (DSM), and Simons Foundation (DSM).